Les chantiers de l’histoire du droit de l’esclavage - Jean-François Niort (Clio@Themis)
Despite recent growth of literature on the subject, the yards of French legal history of slavery remains. Beyond his most famous text, namely the edict of March 1685 called “Code Noir”, whose legal meaning is more complex and nuanced than what could be said the prevailing view, and whose normative content remains also uncertain, it is the complete set of legal texts, both those from the metropolitan and the local authorities, which have to be removed from the archives and analyzed systematically, and then compared to the practices of each colonial territory.